The Impact Assessment of the Community Extension Services: A Case Study of the College of Health Sciences on the Residents of Sta. Justina, Buhi, Camarines Sur, Philippines - Malabanan, Leni M.; Dacara, Jhessa M. (The Indonesian Institute of Science and Technology Research, 2024)
This study explores the demographic profile of respondents from Barangay Sta. Justina focuses on educational attainment, civil status, family size, sources of income, monthly income, housing, types of dwellings, and sources of water supply. Data collection revealed that the majority of respondents are high school graduates, with a significant portion also having college-level education. Most respondents are married, and family sizes vary, with a notable presence of both males and females in households. The primary sources of income include farming, homemaking, and construction work, while construction work also serves as a major secondary income source. Monthly incomes primarily fall within the Php 4,501-5,500 range. Housing data indicates that most respondents own their homes, with a smaller percentage living with relatives or renting. Permanent types of dwellings are the most common, and the primary source of water supply is individual water facilities, supplemented by communal sources and deep wells. The findings provide a comprehensive overview of the socio-economic conditions in Barangay Sta. Justina highlights the intersection of various social determinants that influence the well-being of the community.